Thursday
March 23, 2017

Post a New Question

Posted by on Tuesday, July 26, 2011 at 4:03pm.

Reiny can you show me how to check this problem.
5a^8-20a^7-25a^6

=5a^6(a^2-4a-5)

=5a^6(a^2-5a+a-5)

=5a^6(a(a-5)+1(a-5)

=5a^6(a-5)(a+1) (answer)

  • Math - , Wednesday, July 27, 2011 at 3:06pm

    The GCF is always = to 0r less than the smallest coefficient:

    GCF =< 5.

    When a variable is involved, choose the
    common variable of lowest degree(smallest exponent). All of this has been properly done.

    Answer check:

    Perform the multiplication; the product
    should be identical to the expression
    that was given.

    5a^6(a-5)(a+1) =
    (5a^7-25a^6)(a+1) =
    5a^8 + 5a^7 - 25a^7 -25a^6 =
    Combine like-terms:
    5a^8 - 20a^7 - 25a^6.

    Your answer is correct!

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question